2010
DOI: 10.13109/prkk.2010.59.10.775
|View full text |Cite
|
Sign up to set email alerts
|

Emotionsregulationsstrategien und aggressives Verhalten im Kindergartenalter

Abstract: Emotionsregulationsstrategien und aggressives Verhalten im KindergartenalterPraxis der Kinderpsychologie und Kinderpsychiatrie 59 (2010) Emotionsregulationsstrategien und aggressives Verhalten im KindergartenalterJohanna Helmsen und Franz Petermann Summary Emotion Regulation Strategies and Aggressive Behavior of Preschool ChildrenThe present study (N = 193) examined use of emotional regulation strategies in physically and relationally aggressive preschool children (mean age: 55 months), compared to non-aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…In this context, repeated attempts at securing social support, despite having noticed that no help can be expected, is not considered an adaptive strategy. Consistent with this reasoning, studies that observed children in a frustrating situation in which social support was not available or only to a limited degree, did not find associations between the strategy seeking support and aggression (Gilliom et al, 2002 ; Helmsen and Petermann, 2010 ). Thus, in line with the classification of regulation strategies by other authors (Grob and Smolenski, 2005 ), we considered this strategy to be neither adaptive nor maladaptive in our behavioral observation measure, although it may well be adaptive in other contexts in which support is actually available.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…In this context, repeated attempts at securing social support, despite having noticed that no help can be expected, is not considered an adaptive strategy. Consistent with this reasoning, studies that observed children in a frustrating situation in which social support was not available or only to a limited degree, did not find associations between the strategy seeking support and aggression (Gilliom et al, 2002 ; Helmsen and Petermann, 2010 ). Thus, in line with the classification of regulation strategies by other authors (Grob and Smolenski, 2005 ), we considered this strategy to be neither adaptive nor maladaptive in our behavioral observation measure, although it may well be adaptive in other contexts in which support is actually available.…”
Section: Introductionmentioning
confidence: 86%
“…Different authors have conceptualized anger expression and anger regulation as distinct constructs and have considered anger expression as the outcome of the regulation process or as an indicator of anger reactivity (Melnick and Hinshaw, 2000 ; Dearing et al, 2002 ). However, as we assume that such behavior includes the attempt to reduce the anger intensity, in line with other authors (Grob and Smolenski, 2005 ; Helmsen and Petermann, 2010 ), we consider external anger-related behavior, such as venting the anger, as part of anger regulation.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations